Determinants of seasonal feeding of the generalist snail Arianta arbustorum at six sites dominated by Senecioneae - Hägele, Bernd F.; Rahier, Martine (My University, 2001)
We investigated the diet constituents of Arianta arbustorum by means of faecal analysis and regressed their quantity on the availability and quality of food plants. We studied six sites, all dominated by plants from the Asteraceae tribe Senecioneae, early and later in the growing season, predicting that the snail's food choice would be determined by the presence of the different secondary compounds found in the Senecioneae. The snails consumed less green plant material and more leaf litter in May than in July. Plant water and nitrogen content were higher in May. For the May samples, regressions were only significant at sites that excluded Adenostyles alliariae and Adenostyles alpina; in July, the regression fit was higher at all sites. Of the measured plant parameters, only quantity (availability) was a consistently significant variable in the regressions. Circumstantial evidence suggested that plant secondary compounds had a major influence on snail food choice: fresh-plant consumption increased over the season, as the concentration of many secondary compounds decreased; both plant availability and quality could only explain about half of the observed variation in snail feeding, which argues for other hidden factors influencing snail feeding; the dynamics of feeding of the various senecionean plants were such that A. alliariae and Senecio sp. had a seasonal acceptance whereas Petasites albus was always and A. alpina never accepted, and, finally, the detection of a number of snail-deterrent fractions in A. alpina leaves, a plant which was never found to be consumed in this study.
Keywords: Snails; Secondary plant compounds; Foodquality; Food availability; Senecioneae